Insertion Des Jeunes Déscolarisés Dans La Médecine Traditionnelle En Côte d’Ivoire : Activation Des Ressources Relationnelles Et Ideologiques Comme Strategie - Adrien Kouakou Koua; Léopold Yao Yao; Gérard Kouakou N’Goran (European Scientific Journal, ESJ, 2016)
This study highlights the resources mobilized by school youth for their inclusion in the activities of traditional medicine. It presents the results of a survey conducted in the district of Abidjan in 2015, with a target population of 223 actors of traditional medicine and mobilizes interactionnist strategic analysis to make sense of the phenomenon under study. Thus it is clear from this study that the school youth encountered in this activity, mostly have primary education (60.54%), and to a lesser extent the secondary level (32.63%). They are also, traditional medicine sellers; and mostly professional experience of at least 5 years and over (65.92%). For inclusion in the traditional therapy, it appears that these have recourse to relational resources, as ideological resources or ideological productions. Thus, these resources together, are proving highly strategic for their integration into traditional therapy.